EFFECT OF ALTERNATE WETTING AND DRYING IRRIGATION ON YIELD AND QUALITY OF RABI RICE( Oryza sativa L.) UNDER VARIED NITROGEN LEVELS - P.RAGHUVEER RAO, K.SRIDHAR, A.SRINIVAS, K.AVIL KUMAR, T.RAMPRAKASH and (The Journal of Research, PJTSAU, 2019)
Â A field experiment was conducted during rabi 2016-17 and 2017-18 at Agricultural Research Institute Main Farm, Rajendranagar, Hyderabad, on a clay loam soil to study the effect of alternate wetting and drying irrigation on rabi rice under varied nitrogen levels. The experiment consisted of three irrigation regimes (recommended submergence of 2-5 cm water level as per crop growth stage, AWD irrigation of 5 cm when water level drops to 3cm in water tube, AWD irrigation of 5cm when water level drops to 5cm in water tube) as main plot treatments and three nitrogen levels (120, 160 and 200 kg N ha-1) as sub plot treatments laid out in split plot design with three replications. Significant improvement in yield and quality parameters of rice except protein content, amylose content was observed with recommended submergence of 2 to 5 cm water level as per crop growth stage which was on par with AWD irrigation of 5 cm when water level drops to 3cm in water tube. Among nitrogen levels, application of 200 kg N ha-1 resulted in significantly higher yield and quality parameters except hulling percent, milling percent and head rice recovery of rabi rice which was on par with application of 160 kg N ha-1.